The discovery of the teaching values: a pedagogical vision from the strategy of the disco-forum (Journal of Parents and Teachers, 2014)
"Disco-forum" is the educational activity, done by groups, that through songs and music tries to discover and reflect on the realities that are lived in society. This activity, among other things, helps to foster a critical spirit in the process of communication and to understand the importance of cooperation. Songs improve communication and can refer to the individual's own experiences.
Keywords: Education; song; music; disco-forum; educational activity; communication; society; understanding